Covering Hate: Field Theory and Journalistic Role Conception in Reporting on White Nationalist Rallies. (3rd July 2022) - Perreault, Gregory; Johnson, Brett; Klein, Leslie
ABSTRACT: In the United States, journalists covering white nationalist groups find themselves in an impossible situation: how do you cover the newsworthy rallies—and the concerns raised by the local community—without providing a platform for hate speech? The present study conducts in-depth, semi-structured interviews with 18 journalists who have covered white nationalist rallies. Through the lens of field theory, this study seeks to understand how journalists conceive of their role in such coverage, how they situate themselves within the field, and how they articulate the best practices for this challenging form of reporting. This study finds that white nationalist rallies presented a challenge to journalistic habitus, and journalists responded by drawing from the well of experience and professional socialization.